Dynamics of The Study of The Quran in Indonesia: Language and Paradigm - Muhammad Fajri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This paper describes the development of the study of the Quran in Indonesia. Through historical-analytical approach, it shows that since the arrival of Islam in Indonesia, the study of the Quran has always been developing. They were starting from oral translation until the birth of interpretive products with various dynamics in them. The research question is, what are the forms of the dynamics of the study of the Quran in Indonesia. This study shows that the study of the Quran in Indonesia is moving dynamically, especially in terms of language characters and paradigms. The languages and characters used vary, ranging from Arabic and Arabic script to local-national languages and scripts (Indonesian and Latin characters), such as jawi, lontara, and pegon. Furthermore, the paradigm is also dynamic, such as textual and contextual approaches. The textual approach has characteristics dealing with the linguistic area and historical context of the Quran, not touching the context in which the Quranic verse is studied. Then the contextual approach, which is not only a linguistic aspect but also pays attention to the context both when the Quran was revealed and the context in which the Quran lives, to see the universal meaning of the Quran. In Indonesia, contextual approaches have started in the reformative or modern-contemporary era, at the end of the 20th century AD, and have developed until now.Tulisan ini menjelaskan tentang perkembangan kajian al Quran di Indonesia. Melalui pendekatan historis-analitis dapat diketahui bahwa sejak masuknya Islam ke Indonesia, kajian al Quran selalu mengalami perkembangan. Berawal dari terjemahan secara lisan, hingga lahirnya produk-produk tafsir dengan berbagai dinamika di dalamnya. Pertanyaan yang ingin dijawab dalam penelitian ini adalah terkait apa saja bentuk dinamika kajian al Quran yang terjadi di Indonesia. Hasil penelitian ini menunjukkan bahwa kajian al Quran di Indonesia bergerak dinamis, terutama dalam aspek bahasa-aksara dan paradigma. Bahasa dan aksara yang dipakai beragam, mulai dari bahasa dan aksara Arab sampai pada bahasa dan aksara lokal-nasional (bahasa Indonesia dan aksara latin), seperti aksara jawi, lontara, dan pegon. Sedangkan paradigmapun juga dinamis, yaitu pendekatan tekstual dan kontekstual. Pendekatan tekstual memiliki karaktersitik berkutat pada wilayah linguistik dan konteks sejarah al Quran, tidak menyinggung konteks di mana ayat al Quran itu dikaji. Kemudian pendekatan kontekstual yang tidak hanya aspek linguistiknya saja, tetapi juga memerhatikan konteks saat al Quran itu diturunkan maupun konteks dimana al Quran itu hidup untuk melihat makna universal al Quran. Di Indonesia, Pendekataan kontekstual sudah mulai terjadi di era reformatif atau modern-kontemporer, akhir abad ke-20 M dan berkembang sampai sekarang.